Exploration of strategies to reduce aerosol-spread during chest compressions: A simulation and cadaver model. (July 2020) - Ott, Matthias; Milazzo, Alfio; Liebau, Stefan; Jaki, Christina; Schilling, Tobias; Krohn, Alexander; Heymer, Johannes
Abstract: Objective: To evaluate the effect of strategies to reduce the spread of simulated aerosol during chest compressions on manikin and cadaver experimental models. Methods: To evaluate aerosol-spread we nebulized ultraviolet sensitive detergents into the artificial airway of a resuscitation dummy and performed CPR. The spread of the visualized aerosol was documented by a camera. In a further approach we applied nebulized detergents into the airways of human cadavers and detected the simulated spread on the same way. Among others we did recordings with undergoing compression-only-CPR, with a surgical mask or an oxygen mask on the patients face and with an inserted supraglottic airway device with and without a connected airway filter. Results: Most aerosol-spread at the direction of the provider was visualized during compression-only-CPR. The use of a surgical mask and of an oxygen mask on the patient's face deflected the spread. Inserting a supraglottic airway device connected to an airway filter lead to a remarkable reduction of aerosol-spread. Conclusion: The early insertion of a supraglottic airway device connected to an airway filter before starting chest compression may be beneficial for staff protection during CPR.